ISOLASI SENYAWA ANTIOKSIDAN EKSTRAK ETANOL BUAH BISBUL ( Diospyros discolor Willd.) - Harry Noviardi; Antonius Padua Ratu; Amanda Feby Safitri (Jurnal Farmamedika (Pharmamedika Journal), 2018)
Free radicals are the one form of reactive oxygen compounds, which could disrupt the production of DNA, lipid layer on the cell wall, affecting blood vessels, and the production of prostaglandins. Therefore, it takes antioxidants because its ability to inhibit free radicals by means of donating one electron on free radicals. Synthetic antioxidant compounds often have side effects is not good, so much sought after alternative antioxidants from natural ingredients, one of which is bisbul fruit (Diospyros discolor Willd.). Based on research, bisbul fruit has a strong antioxidant activity. The purpose of this study was to isolate the active compound bisbul fruit extracts which had antioxidant activity. The isolation method used thin layer chromatography method and chromatography columns, continued using FTIR spectroscopy method and LC- MS, while the antioxidant activity using the DPPH method. The results obtained had antioxidant activity IC50 53.51 ppm. The spectrum of FTIR spectroscopy was obtained that the compounds had a hydroxyl group which could be assumed as a phenol or alcohol. While the results of the LC-MS spectrum of compounds having a molecular mass of (m+H+) 631.95 m/z. The results showed extract the ethanol bisbul fruit had a strong antioxidant activity and possibility compound antioxidants was Goshonoside F4